Pengembangan Produk Mesin Press Briket Arang Tempurung Kelapa - Chrisnady Ramadhan (2020)
Coconut shell is a part of coconut fruit that is usually rarely used again. Indonesia is a country that has a lot of coconut plantations. Therefore, the use of coconut shell should be optimized so that the coconut shell does not become waste. In choosing this, take steps to improve the quality of the briquette press pressing machine using coconut shell charcoal dough from a previously made machine. The purpose of this return is to produce a press machine for printing coconut shell charcoal briquettes capable of printing coconut shell charcoal up to 50 kg / hour. The machine uses a hydraulic jack to lift the thrusters to press briquettes. The hydraulic jack is driven by a motor with a power of 300 watt. The jack is placed under the prop on the thrust which is connected to the engine frame which has dimensions overall of 587.45 x 440 x 797 mm. This machine is made with an estimated price of Rp 2,718,000.